Stressful Life Events, Depression, and Non-Suicidal Self-Injury Among Chinese Left-Behind Children: Moderating Effects of Self-Esteem - Lan, Tian; Jia, Xuji; Lin, Danhua; Liu, Xia (Frontiers in Psychiatry, 2019)
Using cross-sectional data of the children in the Guizhou Province of China, the present study examined the association between stressful life events and self-esteem, depression, and NSSI. The participants included 1210 children recruited from 4 junior high schools. Self-report questionnaires concerned stressful life-events, self-esteem, depression, and NSSI. Resulted indicated that Chinese left-behind children who faced more stressful life events were more likely to engage in depression and non-suicidal self-injury (NSSI). Moreover, self-esteem moderated the association between stressful life events and depression, and the association between stressful life events and NSSI. For the left-behind children reporting higher levels of self-esteem, the negative effect of stressful life events on depression and NSSI appeared weaker, compared to those who reported lower levels of self-esteem. In addition, the left-behind type also has a moderating effect on the relationship between stressful life events and NSSI. With the increase of stressful life events, the NSSI among one-migrating-parent group grows more rapidly than that among the two-migrating-parents group. The findings suggest that self-esteem and left-behind type are important individual factors for Chinese left-behind children.